Evaluation of the implementation of Batik-skills training program - Hendro Prasetyono; Dedeh Kurniasari; Laila Desnaranti (REID (Research and Evaluation in Education), 2019)
The purpose of this study is to evaluate the implementation of batik skills training program as a recommendation for program improvement. The method used in this research is a qualitative approach using Context, Input, Process, and Product evaluation model. Samples were taken from the Institute of Skills and Training in the areas of Jakarta, Bogor, Depok, Bekasi, and Tangerang. The results of the evaluation components that meet the evaluation criteria are all aspects of the context component, discipline and learning process, while the components of batik teachers' education qualifications, the use of educational facilities and infrastructure standards, curriculum components, program financing, evaluation of learning outcomes, mastery of theoretical competencies, practices, and impacts to program participants have not been met. The batik skills training program needs to be continued with some improvement. It is recommended for the product components, especially on the impact aspects felt by graduates, to be improved.